AERODYNAMIC ENHANCEMENT IN INNER CHANNEL OF TURBINE BLADE - PIOTR KACZYŃSKI (TASK Quarterly, 2015)
This paper presents the numerical and experimental study of the flow structure in a radial cooling passage model of a gas turbine blade. The investigations focus on the flow aerodynamics in the channel, which is an accurate representation of the configuration used in aero engines. The flow structure and pressure drop were measured by classical measurement techniques. The stagnation pressure and velocity measurements in a channel outlet plane were performed. The investigations concerning the flow field and heat transfer used in the design of radial cooling passages are often developed from simplified models. It is important to note that real engine passages do not have perfect rectangular cross sections, but include corner fillets, ribs with fillet radii and special orientation. Therefore, this work provides detailed fluid flow data for a model of radial cooling geometry which possesses very realistic features. The main purpose of these investigations was to study different channel configurations and their influence on the flow structure and pressure losses in a radial cooling passage of a gas turbine blade.